Theoretical and practical aspects of pedagogy and psychology - Spivak V. A., Silina S. N., Novoselov K. A., Morev A. V., Sudakov D. V., Sudakov O. V., Sych G. V., Koreneva A. V., Petrova L. G., Elfimova A. V., Chumakova S. A., Vinogradov V. L., Shatunova O. V., Pozdnyakov A. N., Lavrentev M. V., Sulimin A. N., Korol N. V. (Theoretical and practical aspects of pedagogy and psychology, 2024)
in this paper, we want to present in English the results of our research, which was previously published in Russian, to a wider range of readers, teachers, scientists. The study is devoted to a tool used in the formation of the motivational component of cadets of a maritime university, which has a great importance on the formation of their professional competence, especially when professional training is conducted in a blended format. In the model developed by us for the formation of the motivational component of the professional competence of cadets of a maritime university in a blended learning environment, professiographic monitoring is used as an assessment and diagnostic tool, which is little studied at present. With the help of it, it becomes possible not only to dynamically quantify the level of the motivational component, but also to adjust the educational process.
Keywords: модель; профессиональная компетентность; professional competence; смешанное обучение; model; курсанты; blended learning; мотивационный компонент; cadets; морской вуз; профессиографический мониторинг; motivational component; maritime university; professiographic monitoring